1984
DOI: 10.1016/0021-9517(84)90191-x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of methanol decomposition over zinc oxide

Abstract: Tawarah, Khalid Moh'd, "Kinetics and mechanism of methanol decomposition over zinc oxide " (1982). Retrospective Theses and Dissertations. 7547. http://lib.dr.iastate.edu/rtd/7547 INFORMATION TO USERSThis reproduction was made from a copy of a document sent to us for microfilming. While the most advanced technology has been used to photograph and reproduce this document, the quality of the reproduction is heavily dependent upon the quality of the material submitted.The following explanation of techniques is pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(1 citation statement)
references
References 67 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…Kung et al have used the single-crystal surfaces of ZnO to probe the decomposition of CH 3 OH; they showed that the ZnO(0001) surface is the dominant surface for this reaction where the main decomposition product was CO under the conditions of their experiment. The mechanism of methanol decomposition on the binary catalyst and ZnO has been extensively studied. A formate surface species is thought to be a decomposition intermediate on both the binary catalyst and ZnO. Its relevance to the MSR relates to the CO 2 hydrogenation reaction , and its possible role in the water-gas shift reaction, where the binary catalyst is extremely effective in this reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Kung et al have used the single-crystal surfaces of ZnO to probe the decomposition of CH 3 OH; they showed that the ZnO(0001) surface is the dominant surface for this reaction where the main decomposition product was CO under the conditions of their experiment. The mechanism of methanol decomposition on the binary catalyst and ZnO has been extensively studied. A formate surface species is thought to be a decomposition intermediate on both the binary catalyst and ZnO. Its relevance to the MSR relates to the CO 2 hydrogenation reaction , and its possible role in the water-gas shift reaction, where the binary catalyst is extremely effective in this reaction.…”
Section: Introductionmentioning
confidence: 99%